Changes in Chemical Properties of Seed Sprouts of Some Cruciferae and Fabaceae Species and Their Nutritional Value - Arin, Levent; Arici, Muhammet; Polat, Serdar; Ates, Ertan (ANKARA UNIV, FAC AGR, 2014)
The seeds of some species in Cruciferae and Fabaceae (Broccoli, Brussels sprout, soybean, Persian clover) were germinated for sprout consumption either alone or as mixtures under the full day light, 12 hours light + 12 hours darkness and fully darkness conditions in growth chamber at 20 +/- 1 degrees C for 5 days. Protein, sugar and vitamin C contents in all sprouts germinated under light conditions were higher than that of grown under dark conditions. Protein content was between 2.21 g 100 g(-1) (Brussels sprouts) and 8.49 g 100 g(-1) (soybean). The sprouts contained higher amount of sugar than seeds. Vitamin C content of sprouts were approximately three to nine fold higher than their seeds. No significant differences were found between sprouts and their seeds for calcium, phosphorus and potassium contents.
Keywords: Broccoli; Brussels sprout; Soybean; Persian clover; Seed sprout; Germination conditions; GLYCINE-MAX; ALFALFA; CHITOSAN; YIELD; Agriculture